Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To identify the explicit function for the sequence given in the table, we need to observe the pattern in the values of [tex]\( y \)[/tex] with respect to [tex]\( x \)[/tex].
[tex]\[ \begin{tabular}{|c|c|} \hline $x$ & $y$ \\ \hline 1 & 9 \\ \hline 2 & 14 \\ \hline 3 & 19 \\ \hline 4 & 24 \\ \hline 5 & 29 \\ \hline \end{tabular} \][/tex]
First, let's see the changes in the [tex]\( y \)[/tex]-values as [tex]\( x \)[/tex] increases:
- When [tex]\( x = 1 \)[/tex], [tex]\( y = 9 \)[/tex]
- When [tex]\( x = 2 \)[/tex], [tex]\( y = 14 \)[/tex]
- When [tex]\( x = 3 \)[/tex], [tex]\( y = 19 \)[/tex]
- When [tex]\( x = 4 \)[/tex], [tex]\( y = 24 \)[/tex]
- When [tex]\( x = 5 \)[/tex], [tex]\( y = 29 \)[/tex]
We notice that each time [tex]\( x \)[/tex] increases by 1, [tex]\( y \)[/tex] increases by 5. This suggests a linear relationship of the form [tex]\( y = mx + b \)[/tex], where [tex]\( m \)[/tex] is the slope, and [tex]\( b \)[/tex] is the y-intercept.
The slope [tex]\( m \)[/tex] (or the common difference in an arithmetic sequence) is 5 because:
[tex]\[ 14 - 9 = 5, \quad 19 - 14 = 5, \quad 24 - 19 = 5, \quad 29 - 24 = 5 \][/tex]
Now we need to find the y-intercept ([tex]\( b \)[/tex]) of the linear function. For [tex]\( x = 1 \)[/tex], [tex]\( y = 9 \)[/tex]. Using the linear equation form:
[tex]\[ y = mx + b \][/tex]
[tex]\[ 9 = 5(1) + b \][/tex]
[tex]\[ 9 = 5 + b \][/tex]
[tex]\[ b = 4 \][/tex]
However, based on the structure of the options provided, we should express the function with an offset form starting from [tex]\( y \)[/tex] when [tex]\( x = 1 \)[/tex].
By observing the table carefully and analyzing the pattern:
For the sequence, the correct explicit formula is:
[tex]\[ a(n) = 9 + (n-1) \cdot 5 \][/tex]
To confirm this, we check:
- For [tex]\( x = 1 \)[/tex]: [tex]\( 9 + (1-1) \cdot 5 = 9 \)[/tex]
- For [tex]\( x = 2 \)[/tex]: [tex]\( 9 + (2-1) \cdot 5 = 14 \)[/tex]
- For [tex]\( x = 3 \)[/tex]: [tex]\( 9 + (3-1) \cdot 5 = 19 \)[/tex]
- For [tex]\( x = 4 \)[/tex]: [tex]\( 9 + (4-1) \cdot 5 = 24 \)[/tex]
- For [tex]\( x = 5 \)[/tex]: [tex]\( 9 + (5-1) \cdot 5 = 29 \)[/tex]
Thus, the final explicit function that matches the pattern in the table is:
B. [tex]\( a(n) = 9 + (n-1) \cdot 5 \)[/tex]
[tex]\[ \begin{tabular}{|c|c|} \hline $x$ & $y$ \\ \hline 1 & 9 \\ \hline 2 & 14 \\ \hline 3 & 19 \\ \hline 4 & 24 \\ \hline 5 & 29 \\ \hline \end{tabular} \][/tex]
First, let's see the changes in the [tex]\( y \)[/tex]-values as [tex]\( x \)[/tex] increases:
- When [tex]\( x = 1 \)[/tex], [tex]\( y = 9 \)[/tex]
- When [tex]\( x = 2 \)[/tex], [tex]\( y = 14 \)[/tex]
- When [tex]\( x = 3 \)[/tex], [tex]\( y = 19 \)[/tex]
- When [tex]\( x = 4 \)[/tex], [tex]\( y = 24 \)[/tex]
- When [tex]\( x = 5 \)[/tex], [tex]\( y = 29 \)[/tex]
We notice that each time [tex]\( x \)[/tex] increases by 1, [tex]\( y \)[/tex] increases by 5. This suggests a linear relationship of the form [tex]\( y = mx + b \)[/tex], where [tex]\( m \)[/tex] is the slope, and [tex]\( b \)[/tex] is the y-intercept.
The slope [tex]\( m \)[/tex] (or the common difference in an arithmetic sequence) is 5 because:
[tex]\[ 14 - 9 = 5, \quad 19 - 14 = 5, \quad 24 - 19 = 5, \quad 29 - 24 = 5 \][/tex]
Now we need to find the y-intercept ([tex]\( b \)[/tex]) of the linear function. For [tex]\( x = 1 \)[/tex], [tex]\( y = 9 \)[/tex]. Using the linear equation form:
[tex]\[ y = mx + b \][/tex]
[tex]\[ 9 = 5(1) + b \][/tex]
[tex]\[ 9 = 5 + b \][/tex]
[tex]\[ b = 4 \][/tex]
However, based on the structure of the options provided, we should express the function with an offset form starting from [tex]\( y \)[/tex] when [tex]\( x = 1 \)[/tex].
By observing the table carefully and analyzing the pattern:
For the sequence, the correct explicit formula is:
[tex]\[ a(n) = 9 + (n-1) \cdot 5 \][/tex]
To confirm this, we check:
- For [tex]\( x = 1 \)[/tex]: [tex]\( 9 + (1-1) \cdot 5 = 9 \)[/tex]
- For [tex]\( x = 2 \)[/tex]: [tex]\( 9 + (2-1) \cdot 5 = 14 \)[/tex]
- For [tex]\( x = 3 \)[/tex]: [tex]\( 9 + (3-1) \cdot 5 = 19 \)[/tex]
- For [tex]\( x = 4 \)[/tex]: [tex]\( 9 + (4-1) \cdot 5 = 24 \)[/tex]
- For [tex]\( x = 5 \)[/tex]: [tex]\( 9 + (5-1) \cdot 5 = 29 \)[/tex]
Thus, the final explicit function that matches the pattern in the table is:
B. [tex]\( a(n) = 9 + (n-1) \cdot 5 \)[/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.